Estimation of Flood Hydrograph for Aquban Catchment Area Using Two Models. - Sarkawt Hamarahim Muhammad; Abdulla A. Abo; Yaseen Wsu Azeez (Zanco Journal of Pure and Applied Sciences, 2023)
The construction of the flood hydrograph in an ungagged catchment area is a challenging portion of the hydrological analysis for design any hydraulic structure. The geomorphologic instantaneous unit hydrograph (GIUH) and Hydrologic Engineers Center (HEC-1) models are widely used for this purpose. The GIUH model simulates flood hydrographs, and the parameters are influenced by the geomorphological features of the area which is based on the probability density function of excess rainfall reaching the catchment. The flood hydrograph is also generated using the HEC-1 model, which is a deterministic hydrological model for simulating rainfall-runoff processes. The nearest station to the Aquban catchment area is Shaqlwa meteorological station that recorded maximum daily rainfall 128.5mm in 2016. The resulting flood hydrographs for the Aquabn catchment area are compared between the GIUH model and the HEC-1 model, with peak discharge and time to peak being the main parameters analyzed. The peak flow of GIUH model is 303.7 m3/s with a time to peak of 1.2 hours, while the HEC-1 model produced a peak discharge of 293.6 m3/s with time to peak of 1.33 hours.